The Insula: An Underestimated Brain Area in Clinical Neuroscience, Psychiatry, and Neurology - Namkung, Ho; Kim, Sun-Hong; Sawa, Akira (Trends in neurosciences (Regular ed.), 2017)
Supported by recent human neuroimaging studies, the insula is re-emerging as an important brain area not only in the physiological understanding of the brain, but also in pathological contexts in clinical research. In this opinion article, we briefly introduce the anatomical and histological features of the human insula. We then summarize the physiological functions of the insula and underscore its pathological roles in psychiatric and neurological disorders that have long been underestimated. We finally propose possible strategies through which the role of the insula may be further understood for both basic and clinical neuroscience. Supported by recent human neuroimaging studies, the insula is re-emerging as an important brain area not only in the physiological understanding of the brain, but also in pathological contexts in clinical research. The anterior insula has a core role in supporting subjective feeling states. It can also regulate the introduction of feelings into cognitive and motivational processes. Understanding of mental conditions through multiple distinct dimensions of function associated with the insula may be important. To overcome the limitations in human neuroimaging studies, computational and statistical efforts in human brain image processing and analysis are expected. With recent technological advances in preclinical studies using rodents, we expect a better understanding of causal roles for the insula in higher brain function. Such understanding consists of the information at multiple levels spanning from the gene, molecule, cell, circuitry, physiology to behavior.